PENGARUH INDIKATOR FUNDAMENTAL DAN MAKROEKONOMI TERHADAP HARGA SAHAM YANG TERGABUNG DALAM ISSI - Siti Rokhaniyah (AKUNTANSI DEWANTARA, 2020)
This study examined the effect of fundamental and macroeconomic indicators on the stock prices of companies listed in the Indeks Saham Syariah Indonesia (ISSI). Fundamental indicators were proxied by EPS, PER, ROE, and DER. Meanwhile, macroeconomic indicators are represented by inflation and world oil prices. This study uses a quantitative approach with penel data regression analysis. The model was determined by the results of the chow test, the hausman test, and the langrange multiplier test. The samples used are manufacturing companies registered with ISSI. With a purposive sampling technique, 41 companies were selected as samples. Data is taken from the financial statements of each company in the 2011-2018. The results of panel data regression analysis (fixed effect) show that EPS, ROE, and inflation have a positivelt effected on ISSI stock prices, while DER and world oil prices have a negatively effected on ISSI stock prices. PER has no effected on ISSI stock prices.